Method for preparing furan through gas-phase decarbonylation reaction of furfural
The catalyst is prepared by using a fibrous activated alumina support prepared by phase change of sodium alumina template in the furfural gas-phase decarbonylation reaction, combined with impregnation method of platinum and palladium precious metal components, which solves the problems of low selectivity and short life of the existing catalysts, and achieves high-efficiency and stable catalytic effect.
Patent Information
- Application Number
- CN202311711680.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2025-06-13
AI Technical Summary
The existing furfural gas-phase decarbonylation catalysts with alumina as support have problems such as low furan selectivity and short catalyst lifetime.
A fibrous activated alumina support was prepared by using sodium alumina as a template phase change, and platinum and palladium were used as biactive metal components to prepare the catalyst by impregnation method. The loading of precious metals Pd and Pt was 0.15-0.3%, and the loading of the additives potassium and sodium was 1.0-20%.
The furan selectivity and service life of the catalyst are significantly improved, and the preparation method is simple, the operating conditions are mild, and it is easy to produce industrially.
Smart Images

Figure BDA0004604918290000061 
Figure BDA0004604918290000062 
Figure BDA0004604918290000063
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a catalyst with fibrous activated alumina as a carrier and its application in the gas-phase decarbonylation of furfural to furan, belonging to the technical field of fine chemical industry. Background Art
[0002] Furan is an important chemical raw material, widely used in organic synthesis and pharmaceutical production, for the preparation of pyrrole, thiophene, tetrahydrofuran, etc., and its market demand is increasing year by year. Traditional methods for preparing furan include decarboxylation of furoic acid, oxidation of furfural, and petroleum method (oxidation of butadiene). Among them, the first two methods have been phased out due to reasons such as backward technology, poor catalyst activity, and serious pollution. The petroleum method, however, has an unoptimistic market prospect due to the decreasing annual petroleum reserves and increasing prices. The raw material of the furfural decarbonylation method, furfural, comes from agricultural and sideline products, and has advantages such as good catalyst activity, meeting the conditions for industrialization.
[0003] Activated alumina has incomparable advantages as a catalyst carrier compared with other carrier materials due to its good thermal stability, excellent specific surface area, and suitable pore structure. The performance of alumina materials in industrial applications is mainly reflected in the morphology, size, pore structure, crystallinity, etc. of the grains. The large specific surface area of alumina is conducive to better dispersion of the catalyst active components, and the suitable pore structure can ensure the directional entry and transfer of reactants and products. Different primary particle morphologies will also greatly affect the performance of alumina. Alumina is widely used as a furfural decarbonylation catalyst and has achieved good reaction results. For example, Patent CN102000569A discloses a Pd / γ-Al 2 O 3 -MO catalyst (MO is an oxide of K, Cs, Li), the Pd loading reaches 5wt%, reacts under a pressure of 0 - 0.5MPa and at 200 - 259°C, with a furfural conversion rate of 92% - 98% and a furan selectivity of 85 - 94%, and the catalyst life is 100 - 120h. Patent US4780522 discloses a catalyst Pt / γ-Al 2 O 3 -CsCO 3 catalyst, the Pd loading reaches 0.75wt%, at normal pressure, 300 - 360°C, and the furfural volume space velocity is 1.1h -1, under the condition that the molar ratio of furfural to hydrogen is 1.8 / 1.4, the furfural conversion rate is 70%-99%, the average yield of furan is 95%, the catalyst runs for 1430 h, and 175 kg of furan is produced per kilogram of precious metal Pt. CN 101422738A discloses the preparation of a highly efficient catalyst for the gas-phase decarbonylation of furfural to furan. Using activated alumina with a particle size of 1-6 mm as the carrier, the palladium loading is 0.25-0.5% by the traditional impregnation method, and nickel and potassium are used as promoters, which can make the furfural conversion rate reach 98% and the selectivity reach 90%. Patent CN 1030841689 B uses the microemulsion method to prepare the main active component Pd of the catalyst, and then loads it on the alumina carrier. The prepared catalyst has a palladium particle size of less than 10 nm, a narrow distribution and good dispersion; when the palladium loading is 0.2%, under the condition of an airspeed of 0.9 h -1 , the furfural conversion rate reaches 100% and the furan selectivity reaches 93%, but the long-term operation life of the catalyst is not investigated.
[0004] The currently reported furfural gas-phase decarbonylation catalysts using alumina as the carrier can achieve a relatively high furfural conversion rate, but still have problems such as low furan selectivity and short catalyst life. SUMMARY OF THE INVENTION
[0005] The object of the present invention is to overcome the defects of the prior art and provide a catalyst for the continuous gas-phase decarbonylation of furfural to furan. It uses dawsonite as a template for phase transformation to prepare a fibrous activated alumina carrier, and uses platinum and palladium precious metals as double active metal components, and is prepared by the impregnation method; this catalyst has better selectivity and a relatively long service life. The present invention also provides a preparation method for the above-mentioned catalyst for the continuous gas-phase decarbonylation of furfural to furan. To achieve the above object, the present invention adopts the following technical solutions:
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A preparation method of a catalyst using fibrous activated alumina as the carrier and its application in the reaction of furfural gas-phase decarbonylation to furan. The catalyst also includes active component precious metals Pd, Pt and promoters potassium and sodium. The mass of the precious metals Pd, Pt is 0.15-0.3% (preferably 0.18-0.25%) of the total mass of the catalyst. The promoters potassium and sodium exist in the form of salts, and the mass of potassium and sodium salts is 1.0-20% (preferably 5.0-10%) of the total mass of the catalyst.
[0008] The length of the fibrous activated alumina is 20 nm - 100 μm, and the length-to-diameter ratio is greater than or equal to 50 and less than or equal to 5000. The preparation method of the catalyst is characterized in that a salt of a noble metal is first configured into a solution with a certain concentration, the configured solution is impregnated on the fibrous activated alumina support, dried at 100 - 120 °C, and calcined at 250 - 600 °C for 2 - 10 h; then a potassium or sodium salt is configured into a solution with a certain concentration, and then impregnated on the fibrous activated alumina precursor loaded with the noble metal, dried at 100 - 120 °C, and calcined at 250 - 600 °C for 2 - 10 h to obtain the catalyst.
[0009] The preparation method of the catalyst is characterized in that a salt solution of a noble metal is first impregnated on the fibrous activated alumina, dried at 100 - 120 °C, and calcined at 250 - 600 °C; then a salt solution of potassium or sodium is impregnated on the support, dried at 100 - 120 °C, and calcined at 250 - 600 °C for 2 - 10 h to obtain the catalyst.
[0010] The preparation method of the fibrous activated alumina support is characterized by multi-step phase transformation of a sodium aluminate solution. The specific steps are as follows:
[0011] 1) Preparation of dawsonite: While introducing CO into 100 - 1000 mL of sodium aluminate solution (1.0 wt - 20 wt%) at a rate of 100 mL - 2000 mL / min (preferably 500 mL - 1500 mL / min) for 1 - 24 hours, and simultaneously adding sodium carbonate solution (100 - 1000 mL) (150 - 250 g / L, preferably 180 - 220 g / L), maintaining the pH change range at 11.8 - 12.2, reacting at a certain temperature (323 - 373 K, preferably 343 - 363 K) for 2 - 8 hours, filtering after the reaction, and washing with boiling water 3 times to obtain a dawsonite filter cake; 2 100mL - 2000mL / min (preferably 500mL - 1500mL / min) for 1 - 24 hours, while adding sodium carbonate solution (100 - 1000 mL) (150 - 250 g / L, preferably 180 - 220 g / L), maintaining the pH change range at 11.8 - 12.2, reacting at a certain temperature (323 - 373 K, preferably 343 - 363 K) for 2 - 8 hours, filtering after the reaction, and washing with boiling water 3 times to obtain a dawsonite filter cake;
[0012] 2) Preparation of ammonium aluminum carbonate: Add the wet dawsonite filter cake obtained in step 1 to 100 - 2000 mL of (NH 4 ) 2 CO 3 (preferably 100 - 200 g / L)) solution, stir and react at a set temperature (323 - 373 K) (preferably 343 - 363 K) for 2 - 48 hours (preferably 5 - 24 hours), filter after the reaction, wash with distilled water at 323 K 3 times, and dry at 323 - 343 K for 24 h to obtain an ammonium aluminum carbonate filter cake. 3) Preparation of fibrous activated alumina: Heat the ammonium aluminum carbonate in a muffle furnace at a heating rate of 2 K - 5 K / min to a certain temperature (623 - 1073 K) for calcination, keep the sample at the final temperature for 30 - 600 min, and then cool to room temperature to obtain fibrous activated alumina.
[0013] The noble metal palladium salts described are at least one of palladium chloride, palladium nitrate, palladium acetate, chloropalladic acid, sodium chloropalladate, ammonium chloropalladate; the noble metal platinum salts are at least one of chloroplatinic acid, platinum tetrachloride, platinum nitrate, platinum acetylacetonate; the salt solution of potassium or sodium is at least one of carbonate, acetate, sulfate, nitrate, chloride.
[0014] The furfural decarbonylation reaction proceeds according to the following steps: After being heated in a vaporizer, furfural enters the catalyst bed of a fixed-bed reactor together with hydrogen. Furfural undergoes a decarbonylation reaction on the catalyst to produce furan. The liquid raw materials and products are collected as reaction liquid after being condensed at low temperature, and the gas products are quantitatively analyzed by on-line chromatography. The reaction conditions for the preparation of furan by furfural decarbonylation are: atmospheric pressure, the reaction temperature is 250 - 360 °C (preferably 280 - 320 °C), the mass space velocity of furfural feeding is 0.5 - 5.0 h -1 (preferably 1.2 - 3.5 h -1 ), and the molar ratio of hydrogen to furfural is 0.6 - 7.5:1 (preferably 1.5 - 4.5:1).
[0015] The characteristics of this method are: using fibrous activated alumina as the carrier, the prepared catalyst has small, narrow-distributed and well-dispersed main active component particles, with an average particle size of less than 4 nm. When applied to the furfural decarbonylation reaction to produce furan, it has a high furfural conversion rate, high furan selectivity and stability; the preparation method of this catalyst is simple, the operating conditions are mild, and it is easy to produce.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0017] (1), The main active component particles of the catalyst prepared by the present invention are small, narrow-distributed and well-dispersed, with an average particle size of less than 4 nm;
[0018] (2), The present invention uses a catalyst with a low noble metal Pd and Pt loading of 0.15 - 0.25%. Under the condition that the mass space velocity of furfural feeding is 2.32 h -1 (volume space velocity 1.48 h -1 ), the furfural conversion rate is still close to 100%, and the furan selectivity exceeds 99%;
[0019] (3), The preparation method of the catalyst described in the present invention is simple, the operating conditions are mild, and it is easy to produce. Specific embodiments
[0020] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention. The protection scope claimed by the present invention is defined by the appended claims and their equivalents.
[0021] There are no particular restrictions on the purity of all raw materials of the present invention, and the reagents used in the following examples are all commercially available. Qualitative analysis of reaction raw materials and liquid products: Agilent gas chromatography-mass spectrometry technology is used for qualitative analysis of furfural, furan, 2-methylfuran, tetrahydrofuran, 2-methyltetrahydrofuran, furfuryl alcohol, and tetrahydrofurfuryl alcohol. It is confirmed by searching the mass spectrometry library and comparing with the retention time of the reference substance. Quantitative analysis of reaction liquid products: An Agilent gas chromatograph (the chromatographic column is an HP-5 capillary column, with an FID hydrogen flame detector) is used for quantitative analysis of the products by the internal standard method, and the internal standard is n-heptanol. Drawing of the internal standard working curve: Accurately weigh a total of 4.0 g of the reference substances of furfural, furan, 2-methylfuran, tetrahydrofuran, 2-methyltetrahydrofuran, furfuryl alcohol, and tetrahydrofurfuryl alcohol to prepare a standard liquid mother liquor. Then, 0.02 g, 0.05 g, 0.15 g, 0.25 g, 0.45, 0.65, 0.85, and 1.0 g are respectively taken from the mother liquor, and then 0.05 g of n-heptanol is dissolved, and 1.5 mL of ethanol is added for volume fixation. Then, gas phase analysis is carried out, and the peak area ratios (Ai / As, where Ai represents the chromatographic peak area of the analyte and As represents the chromatographic peak area of the reference substance) of the analytes (furfural, furan, 2-methylfuran, tetrahydrofuran, 2-methyltetrahydrofuran, furfuryl alcohol, and tetrahydrofurfuryl alcohol) and the reference substance n-heptanol are respectively recorded as the abscissa, and the mass ratios mi / ms of furfural, furan, 2-methylfuran, tetrahydrofuran, 2-methyltetrahydrofuran, furfuryl alcohol, tetrahydrofurfuryl alcohol, and n-heptanol in each solution are calculated as the ordinate to draw the standard working curve of the raw materials and products, and calculate the amount of the product; Quantitative analysis of reaction gas products: A Panolen gas chromatograph is connected online with a fixed bed reactor (with a TCD\FID hydrogen flame detector), and the products of CO, C2, C3, C4, furan, 2-methylfuran, tetrahydrofuran, and 2-methyltetrahydrofuran are quantitatively analyzed by the external standard method, and the amount of the product is calculated. In the following examples, the conversion rate of furfural and the selectivity and yield of furan are defined by the following formulas:
[0022]
[0023]
[0024]
[0025]
[0026] Yield of 3,4-dihydropyran (%) = Selectivity of 3,4-dihydropyran * Conversion of tetrahydrofurfuryl alcohol * 100
[0027] Yield of tetrahydropyran (%) = Selectivity of tetrahydropyran * Conversion of tetrahydrofurfuryl alcohol * 100
[0028] Selectivity of 2-hydroxytetrahydropyran (%) = Selectivity of 2-hydroxytetrahydropyran * Conversion of tetrahydrofurfuryl alcohol * 100
[0029] Catalyst preparation:
[0030] Preparation of fibrous alumina support:
[0031] The specific process of the fibrous activated alumina support is as follows: 1) Preparation of sodium aluminate hydroxide: Sodium aluminate solution (500 mL, 10 wt%) is bubbled with CO 2 (1000 mL / min), and at the same time, 1000 mL of sodium carbonate solution (150 - 250 g / L) is added, keeping the pH in the range of 11.8 - 12.2. React at a certain temperature (353 K) for 5 hours. After the reaction, filter and wash 3 times with boiling distilled water to obtain a sodium aluminate hydroxide filter cake. 2) Preparation of ammonium aluminum carbonate: Add the wet sodium aluminate hydroxide filter cake to 500 mL of (NH 4 ) 2 CO 3 (30 - 300 g / L) solution, stir and react at 323 K for 24 hours. After the reaction, filter and wash 3 times with distilled water at 323 K, and dry at 323 K for 24 h to obtain an ammonium aluminum carbonate filter cake. 3) Preparation of fibrous activated alumina: Heat the ammonium aluminum carbonate in a muffle furnace at a heating rate of 5 K / min (673 - 1073 K), hold for 30 min, and then cool to room temperature to obtain fibrous activated alumina.
[0032] By adjusting the concentrations of sodium carbonate, (NH 4 ) 2 CO 3 and the calcination temperature of ammonium aluminum carbonate, fibrous activated alumina (FAA) support samples are obtained and labeled as shown in Table 1 below:
[0033]
[0034]
[0035] The obtained fibrous activated alumina has a pore volume of 1.0 - 1.1 mL / g. The equal-volume impregnation method is used, and the pore volume is calculated as 1.1 mL / g. The volume of the impregnating solution is slightly higher than the total volume of the support in actual operation.
[0036] Example A1
[0037] Weigh 11.0 mL of palladium chloride solution (1.0 g of palladium chloride dissolved in 250 mL of dilute hydrochloric acid with a concentration of 49.8 mmol / L). Put 10 g of FAA-1 into the above solution and impregnate for 6 hours. Dry at 120 °C for 12 hours and calcine at 400 °C for 4 hours. Weigh 1.0 g of potassium carbonate, dissolve it with 11.2 g of pure water, impregnate the above palladium-loaded FAA-1 support for 6 hours, dry at 120 °C for 12 hours, and calcine at 400 °C for 4 hours to obtain Catalyst 1#. The loading amount of palladium relative to the support is 0.25%, and the loading amount of potassium salt relative to the support is 10%. After the obtained catalyst is reduced, it is characterized by transmission electron microscopy (TEM), and it is found that the particle size distribution range of metallic palladium is 2 - 6 nm, and almost no agglomerated large particles are formed.
[0038] Example A2: The catalyst support is FAA-2 (instead of FAA-1), and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 2#.
[0039] Example A3: The catalyst support is FAA-3 (instead of FAA-1), and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 3#.
[0040] Example A4: The catalyst support is FAA-4 (instead of FAA-1), and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 4#.
[0041] Example A5: The catalyst support is FAA-5 (instead of FAA-1), and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 5#.
[0042] Example A6: The catalyst support is FAA-6 (instead of FAA-1), and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 6#.
[0043] Example A7: The catalyst support is FAA-7 (instead of FAA-1), and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 7#.
[0044] Example A8: Weigh 6.5 mL of palladium chloride solution, and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 8#. The loading amount of palladium relative to the support is 0.15%.
[0045] Example A9: Weigh 13.0 mL of palladium chloride solution, and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 9#. The loading amount of palladium relative to the support is 0.3%.
[0046] Example A10: Weigh 0.1 g of potassium carbonate, and the others (processes and conditions) are the same as those in Example A1 to obtain Catalyst 10#. The loading amount of potassium salt relative to the support is 1.0%.
[0047] Example A11: Weigh 0.5 g of potassium carbonate. Keep other (processes and conditions) the same as in Example A1 to obtain Catalyst 11#, and the loading amount of the potassium salt relative to the support is 5.0%.
[0048] Example A12: Weigh 2.0 g of potassium carbonate. Keep other (processes and conditions) the same as in Example A1 to obtain Catalyst 12#, and the loading amount of the potassium salt relative to the support is 20%.
[0049] Comparative Example 1: Weigh 11.0 mL of palladium chloride solution (1.0 g of palladium chloride dissolved in 250 mL of dilute hydrochloric acid with a concentration of 49.8 mmol / L). Put 10 g of activated Al 2 O 3 balls (crushed and sieved to 20 - 40 mesh) produced by Shandong Wuhua New Materials Technology Co., Ltd. into the above solution for impregnation for 6 hours, and dry at 120 °C for 12 hours; Weigh 1.0 g of potassium carbonate, dissolve it with 11.2 g of pure water, and impregnate the activated Al 2 O 3 support loaded with palladium for 6 hours, dry at 120 °C for 12 hours, and calcine at 400 °C for 4 hours to obtain Catalyst 13#, with the loading amount of palladium relative to the support being 0.25% and the loading amount of potassium relative to the support being 10%. After the obtained catalyst is reduced, it is characterized by transmission electron microscopy (TEM), and it is found that the particle size distribution range of metallic palladium is 5 - 10 nm, and a few particle sizes grow to about 20 nm.
[0050] Examples B1 - B12
[0051] The above - obtained catalysts were evaluated on a fixed - bed reactor with an inner diameter of 7 mm. The reaction was carried out at atmospheric pressure, the reaction temperature was 265 °C, the mass space velocity of furfural feed was 3.48 h -1 (volume space velocity 2.22 h -1 ), the molar ratio of hydrogen to furfural was 2.46, and the running time was 12 hours. The evaluation results are shown in Table 1.
[0052] The furfural decarbonylation reaction is carried out according to the following steps: Furfural is heated to 40 - 150 °C in a vaporizer and then enters the catalyst bed layer of the fixed - bed reactor together with hydrogen. Furfural undergoes a decarbonylation reaction on the catalyst to generate furan. The liquid raw material and the product are collected by low - temperature condensation after condensation, and the gas product is quantitatively analyzed by on - line chromatography.
[0053] It can be seen from Examples B1 - B7 and Comparative Example 2 in Table 1 that under the same conditions, the catalyst prepared with fibrous activated alumina as the carrier has higher raw material conversion rate and furan selectivity in the catalytic decarbonylation reaction of furfural than that with industrial activated alumina as the carrier. This may be due to the smaller particle size and more uniform distribution of metal ions. From Examples B1, B10 - B12, it can be seen that when the addition amount of the auxiliary component is less than 1%, the furan selectivity decreases, and when the addition amount is higher than 20%, the furfural conversion rate decreases somewhat. The reason for the excellent performance of the catalyst may be that the fibrous activated alumina as the carrier can make the metal particle size smaller and the distribution more uniform.
[0054]
[0055]
[0056] Reaction process of Examples B13 - B20
[0057] For the catalyst - 2# in Example 1, the reaction conditions were changed and the running time was 12 hours. The results are shown in Table 2: It can be seen from Examples B1, B13 - B15 that when the furfural feed space velocity is higher than 4.64 h -1 , not all furfural can be converted. Considering the industrial cost of subsequent product separation and purification, a space velocity of 2.32 h -1 is more appropriate. It can be seen from Examples B14, B16 - 18 that in the temperature range of 265 - 340 °C, all furfural can be converted, providing a relatively wide temperature range for industrial production. It can be seen from Examples B16, B19 - B20 in Table 2 that a hydrogen - to - aldehyde molar ratio of 0.67 - 7.39 is more suitable, and all have excellent performance in the decarbonylation of furfural to produce furan.
[0058]
[0059]
[0060] Example B21
[0061] Under the same reaction process conditions as in Example B16, the reaction was carried out at atmospheric pressure, the mass space velocity of furfural feed was 2.32 h -1 , and the molar ratio of hydrogen to furfural was 2.46. A long - term stability test of catalyst 2# was carried out. The products at the outlet of the hydrogenation reactor were collected for analysis, and the analysis results are shown in Table 3. It can be seen from the data in Table 3 that the catalyst has good stability. After 800 h of reaction, the furfural conversion rate still reaches 92.0%, and the furan selectivity is 97.8%. This further shows that the fibrous activated alumina as the carrier can make the metal particle size smaller and the distribution more uniform, thereby improving the anti - sintering ability of the catalyst, which is the main reason for the long catalyst life.
[0062]
[0063] The above content is a further detailed description of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is only limited to these descriptions. For those of ordinary skill in the technical field to which the present invention pertains, without departing from the concept of the present invention, several simple deductions and substitutions can still be made, and all should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for the gas-phase decarbonylation of furfural to furan, characterized in that: The catalyst used has fibrous activated alumina as the carrier, and the length of the fibrous activated alumina is 20 nm - 100 μm (fiber length), and the aspect ratio is greater than or equal to 50 and less than or equal to 5000. The catalyst also includes one or two of the active components noble metals Pd and Pt, and one or two of the promoters potassium and sodium. The mass of the noble metals Pd and Pt is 0.15 - 0.3% (preferably 0.18 - 0.25%) of the mass of the carrier. The promoters potassium and sodium exist in the form of their oxides or salts, and the loading amount of the promoter is 1.0 - 20% (preferably 5.0 - 10%) of the total mass of the catalyst carrier.
2. The method according to claim 1, characterized in that: The preparation process of the catalyst is as follows: First, a salt of a noble metal is configured into a solution, and the configured solution is impregnated on the fibrous activated alumina carrier, dried at 100 - 120 °C, and calcined at 250 - 600 °C for 2 - 10 h; then a potassium and / or sodium salt is configured into a solution, and then impregnated on the fibrous activated alumina precursor loaded with the noble metal, dried at 100 - 120 °C, and calcined at 250 - 600 °C for 2 - 10 h to obtain the catalyst.
3. The method according to claim 1 or 2, characterized in that: The preparation process of the fibrous activated alumina carrier is carried out through multiple phase transformations of sodium aluminate solution. The specific steps are as follows: 1) Preparation of dawsonite: 100 - 1000 milliliters of sodium aluminate solution (1.0 wt% - 20 wt%) is introduced with CO 2 at 100 mL - 2000 mL / min (preferably 500 mL - 1500 mL / min) for 1 - 24 hours, and at the same time, sodium carbonate solution (100 - 1000 milliliters) (150 - 250 g / L, preferably 180 - 220 g / L) is added. The pH change range is maintained at 11.8 - 12.2, and the reaction occurs at a certain temperature (323 - 373 K, preferably 343 - 363 K) for 2 - 8 hours. After the reaction, filtration is carried out, and it is washed with boiling water 1 - 5 times to obtain a dawsonite filter cake; 2) Preparation of ammonium aluminum carbonate: Add the wet natrolite filter cake obtained in step 1 to 100 - 2000 milliliters of (NH 4 ) 2 CO 3 (30 - 300 g / L, preferably 100 - 200 g / L)) solution, stir and react at a set temperature (323 - 373 K) (preferably 343 - 363 K) for 2 - 48 hours (preferably 5 - 24 hours). After the reaction, filter, wash with water at 40 - 100 °C for 1 - 5 times, and dry at 323 - 343 K for 8 - 24 h to obtain an ammonium aluminum carbonate filter cake; 3) Preparation of fibrous activated alumina: Ammonium aluminum carbonate is calcined in a muffle furnace at a heating rate of 2 K - 5 K / min to a certain temperature (523 - 1073 K, preferably 623 - 873 K), the sample is maintained at the final temperature for 30 - 600 min, and then cooled to room temperature to obtain fibrous activated alumina.
4. The method according to claim 2, characterized in that, The noble metal palladium salt is at least one or more of palladium chloride, palladium nitrate, palladium acetate, chloropalladic acid, sodium chloropalladate, ammonium chloropalladate; the noble metal platinum salt is at least one or more of chloroplatinic acid, platinum tetrachloride, platinum nitrate, platinum acetylacetonate; the potassium or sodium salt is at least one or more of carbonate, acetate, sulfate, nitrate, chloride.
5. According to the method described in claim 1, characterized in that, The reaction conditions for the decarbonylation of furfural to furan are as follows: at atmospheric pressure, the reaction temperature is 250 - 360 °C (preferably 280 - 320 °C), and the mass space velocity of furfural feed is 0.5 - 5.0 h -1 (preferably 1.2 - 3.5 h -1 ), and the molar ratio of hydrogen to furfural is 0.6 - 7.5:1 (preferably 1.5 - 4.5:1).
Citation Information
Patent Citations
Efficient furan preparation catalyst by furfural decarbonylation
CN101422738A
Catalyst for producing furan by furfural liquid-phase decarbonylation and preparation method
CN102000569A